Breeding for blast resistance in rice in West Africa - Singh, B.N.; Jones, M.P.; Fomba, S.N.; Sere, Y.; Sy, A.A.; Akator, K.; Ngninbeyie, P.; Ahn, S.W. (Springer, 2000)
Rice is grown in an area of 4.3 million ha in 17 WARDA member countries of West Africa (FAO, 1994). The total annual production is 7.4 million tons of paddy with an average yield of 1.7 tons ha−1, which is the lowest compared to other rice growing regions of world.The rice import in WARDA member states in 1995 was 2.43 million tons with a value of 684 million US$ (WARDA Data Base, 1998). The average yield in the region is low due to presence of many biophysical constraints, which reduces the yield potential of the varieties. Rice blast (Pyricularia grisea) is one of the major biotic constraints affecting rice production. It is a widespread and most serious disease in all the rice growing ecologies (Awoderu, 1974; Bidaux, 1978; John et al., 1985; Fomba and Taylor, 1994). Seedling blast occurs in nursery stage in transplanted rice, leaf blasts under direct seeded uplands and rainfed lowlands, and panicle blasts in all the ecologies.